Strengthening Islamic Education Motivation in the Community: A Community Service Initiative at TPQ Arrizqy - Fifi Julfiati; Kusumawati; Ichwan Nugroho (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
ABSTRACTThe community service activity conducted aimed to provide socialization on the Motivation of Islamic Education to the community at TPQ Arrizqy. This community service was carried out at TPQ Arrizqy, located at Griya Salak Endah 2, Block E 1, Number 5, RT 05, RW 10, Cinangka Village, Ciampea District, Bogor. The methods used in the implementation of this community service included: 1) Observation, by inviting parents of students and members of the Griya Salak Endah 2 Islamic study group (majlis ta’lim) to participate in the activity; 2) Preparation stage, where Fifi Julfiati, A.KS., M.Si, as the facilitator, prepared the necessary equipment and materials for the community service; 3) Implementation stage, where teachers, parents of students, and members of the Griya Salak Endah 2 Islamic study group began the activity with the recitation of tawassul and opening prayers, followed by the presentation and socialization of the material on the theme "Motivation of Islamic Education in the Arrizqy Community" by speakers Mr. Ichwan Nugroho, M.M., and Kusumawati, S.IP., M.A.; 4) Discussion stage, where the community service team, parents of students, and members of the Griya Salak Endah 2 Islamic study group interacted through a Q&A session related to the topic; 5) Evaluation stage, where the community service team evaluated the activity using observation sheets to improve future community service activities at TPQ Arrizqy. The expected outcomes of this community service activity are: 1) to enhance knowledge and provide benefits for teachers, lecturers, and students to be applied in the teaching and learning process; 2) the publication of articles and journals. Keywords: Motivation, education, Islam, TPQ, community.